Implementasi Model Inkuiri Terbimbing Berbantuan Virtual Lab Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas XI Pada Materi Gelombang Cahaya - Diyah Prasasti Listiantomo; Dwikoranto (UNIB Press, 2023)
This research was conducted with the aim of analyzing the implementation of the virtual lab-assisted guided inquiry model to analyze the results of increasing critical thinking skills in class XI students after implementing the virtual lab-assisted guided inquiry model on the material of light waves. GroupDesign. The subjects used in this study were 60 class XI students. The instruments used in this study were pretest and posttest question sheets. The data obtained in this study were tested by prerequisite tests on pretest and posttest values which included normality tests and homogeneity tests, then different tests were carried out with dependent t-tests, independent t-tests and N-Gain tests. Based on the results and discussion of the research, it can be concluded that the results of increasing the critical thinking skills of class XI students in the light wave material after implementing the virtual lab-assisted guided inquiry learning model experienced a significant increase and are in the high category. In the control class, the results of increasing the critical thinking skills of class XI students in the light wave material after the implementation of the conventional learning model experienced a significant increase and were in the high category. There is a difference in the results of increasing critical thinking skills in the experimental and control classes as shown by the independent t-test which produces Â Â = 5,72 Â 2.